Transcaruncular Medial Wall Orbital Decompression: An Effective Approach for Patients with Unilateral Graves Ophthalmopathy - Robert H. Hill; Craig N. Czyz; Thomas A. Bersani (The Scientific World Journal)
Purpose. To evaluate the reduction in proptosis, incidence of postoperative diplopia, and postoperative globe symmetry after transcaruncular medial wall decompression in patients with unilateral Graves ophthalmopathy. Methods. Retrospective review of 16 consecutive patients who underwent unilateral transcaruncular medial wall orbital decompression from 1995 to 2007. The diagnosis of Graves ophthalmopathy was based on history and clinical findings including proptosis, lagophthalmos, lid retraction, motility restriction, and systemic thyroid dysfunction. Results. The mean reduction in proptosis was 2.3 mm. The mean difference in exophthalmometry preoperatively between the two eyes in each patient was 3.1 mm whereas postoperatively the mean difference was 1.1 mm (P=0.0002). Eleven of 16 patients (69%) had 1 mm or less of asymmetry postoperatively. There was no statistically significant difference in the incidence of diplopia pre- and postoperatively (P=1.0). Conclusions. Medial wall orbital decompression is a safe and practical surgical approach for patients with unilateral Graves orbitopathy. The procedure carries a low risk of morbidity and yields anatomic retrusion of the globe that is comparable to other more invasive methods and may yield more symmetric postoperative results.